Implementasi E-learning Dikaitkan Dengan Pengembangan Higher Order Thinking Skills - Fikri Aulia; Wikan Budi Utami; ponoharjo ponoharjo (Institut Pendidikan Indonesia, 2020)
Abstact — This research is based on the rapid Information and Communication Technology in the world of education. This is contrary to the concept of 21st century competence, one of which is mastering Information and Communication Technology. This research is motivated by the weakness of high level thinking skills or High Level Thinking Skills in FKIP Universitas Pancasakti Tegal students, specifically students in mathematics education. The purpose of this research is to study the implementation of E-learning based learning in improving Higher Level Thinking Skills in FKIP UPS Tegal students. This type of research is research and development. Affirmed by Borg and Gall (2003), that